Prototipe Lembar Kerja Peserta Didik Matematika Berbentuk Elektronik Berbasis Tri N pada Pokok Bahasan Bilangan Bulat dan Pecahan - Maharani Wahyu Saputri; Tri Astuti Arigiyati; Sri Adi Widodo (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2022)
This study aims to (1) design an electronic mathematical student worksheet based on Tri N on the subject of integers and fractions; (2) knowing the level of validity of the electronic mathematics student worksheets based on the Tri N. The stages of this research use Define, Design, and Develop, which are part of the 4D stage of RND. The data collection technique used at the define stage is documentation and journal analysis, while at the develop stage is a validation sheet filled out by validators (math teachers and mathematics education lecturers). The data analysis technique carried out at the define and design stages is descriptive qualitative, while at the develop stage is a quantitative descriptive analysis using Aiken validity. The results showed that the design process obtained a mathematics learning tool in the form of Mathematics E-LKPD which was suitable for use. This can be seen from the results of the V-Aiken calculation obtained in the range of 0.691 to 0.988.